Sweet pepper (Capsicum annuumL.) breeding on yield and fruits qualityaccording to the cultivar model for unheated soil greenhouses - N. A. Niavestsenka; I. G. Puhachova; M. M. Dabrodzkin; A. V. Kilchevsky (Овощи России, 2023)
Relevance. An important proviso for the commercially effective cultivation of vegetable crops in different types of greenhouses is high yield, which significantly depends on modern cultivars with different characteristics and properties. When creating a new cultivar, it is necessary to present its model in accordance with the expected ecological and agrotechnical conditions of planting, the purpose of use, the level of manifestation of morphological and biochemical characteristics, which together will ensure a high yield. The goal of research – to create early ripening, high-yielding cultivars of sweet pepper with high taste assessment of fresh fruits and content of biologically valuable substances.Materials and methods. The studies were conducted in 2015-2018 and 2020-2021 in the Belarusian State Agricultural Academy. The objects were 46 breeding lines of sweet pepper. An evaluation of fruits and plants morphological characteristics, yield traits, fruits biochemical composition, and tasting were carried out.Results. Valuable lines for breeding were selected with a gross yield of 5.60–6.71 kg/m2, with large fruits (150–220 g), thick pericarp (>7 mm),with a high content of biologically valuable substances and fruit quality 4.3–4.7 points. Lines with a complex of economically valuable traits including high tasting score, were transferred to the State Inspection for Testing and Protection of Plant Varieties and recommended for commercial use in the Republic of Belarus under the names Altyn, Chervonets, Karat, Goretsky Krasny, Garlachyk Zhovty and Chyrvony Magnat.